2, 2′-Disilylazobenzenes featuring double intramolecular nitrogen⋯silicon coordination: a photoisomerizable fluorophore1. Issue 37 (7th October 2015) - Kano, Naokazu; Yamamura, Masaki; Kawashima, Takayuki
<x xml:space="preserve">Abstract</x> Fluorescent (E)-4, 4′-dimethyl-2, 2′-bis(trimethylsilyl)azobenzene was synthesized.